Challenges and opportunities of corporate governance transformation in the digital era - Kuznetsov, Mikhail Yevgenievich, 1979-; Nikishova, Maria Igorevna, 1942- (Advances in business strategy and competitive advantage., 2020)
"This book analyzes corporate governance transformation under the pressure of new technologies and economic changes"--